Optimalisasi Hak Asasi Manusia dan Hukum Gender Pasca Terbitnya Peraturan Menteri Pendidikan Kebudayaan dan Teknologi Republik Indonesia Nomor 30 tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi - Ayu, Navirta Ayu (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2022)
This research is a doctrinal research, or often also referred to as normative research, which is a study of the law that is conceptualized and developed on the basis of the doctrine adopted by the conceptor and or its development and form of implementation. In the doctrine of positivism, law is conceptualized as a rule of law. Therefore, doctrinal legal research in the positivism tradition is focused on written law, in this case laws and regulations, especially legislation relating to the optimization of human rights and gender law after the issuance of Permenristekdikti Number 30 of 2021 concerning the Prevention and Handling of Violence. Sexuality in College Environment. In addition to criticizing the laws and regulations, they also look at how the implementation of these laws and regulations are and see what are the obstacles in realizing justice regarding the prevention and handling of sexual violence in universities. The result of this study is that sexual violence is targeted at vulnerable groups. Most of the victims were women and children. Women and children are part of a vulnerable group of people and are entitled to special treatment and protection under human rights laws and regulations because of their vulnerability. Special precautions relating to the protection of women and children who are victims of sexual violence are very important. Higher education as an institution of access to education which is a constitutional right of citizens is obliged to become a safe space for the entire academic community from sexual violence; tertiary institutions are required to guarantee the rights of the academic community in studying and working in an effort to protect against sexual violence, including the protection and guarantee of academic rights